Ground reaction force comparison between both feet during giant slalom turns in alpine skiing - Falda-Buscaiot, T.; Hintzy, F.; Coulmy, N. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to measure the difference in normal force under both feet during alpine skiing giant slalom turns. Eleven experienced alpine skiers performed a giant slalom course at race intensity. All trials were recorded synchronously using a video camera and a plantar pressure measuring system. The mean force on the grouped two feet varied from 0.7 BW at the start of a turn to 1.5 BW during the steering phase of a turn performed in a steep slope condition. When skiing on FLAT slope condition, it reached only 1.3 BW. Results also showed that the outside foot receives significantly more pressure than the inside foot during the entire turn except the initiation phase. This last finding is not affected by slope steepness.